Impact of Motor Vehicle Emissions on Air Quality in Urban and Sub Urban Area - A. Ikhsan Karim; Sugito SUGITO (Bandar Lampung University (UBL), 2014)
One of the effects of development and growth in urban areas is the increasing number of vehicles from year to year . Improved transportation needs to support the activities of the community , the problems faced by large cities today . Along with these problems , the most crucial in the presence of the number of vehicles is the problem of congestion .Vehicle congestion and concentrated on a spot will cause air pollution . Air pollution comes from motor vehicle exhaust emissions contain toxic substances that are harmful to human health , among others , CO, HC, CO2, SOx, NOx, PM10 .JICA study said 70 % of air pollution occurs in urban contributed from motor vehicles , and the remaining 30% are caused by industrial and household activities .Based on these facts , the government sought to continue to make prevention of air pollution in accordance with the mandate of Law No. 32/2009 about Protection and Management of the Environment and Government Regulation No. 41/1999 about Air Pollution Control. In addition , more specific regulation No.5/MENLH/2006 , regulates the Threshold Motor Vehicle Exhaust Emissions that can be used as a legal basis so that exhaust emissions from motor vehicles do not pollute the air . Air pollution control efforts are primarily aimed at improving air quality for human life.Referring to the importance of the above issues , this study will examine the effect of vehicle emissions on air quality in Urban and Sub- Urban areas in the city of Bandar Lampung.This study uses primary and secondary data , which begins with a review of the concept of the development of Bandar Lampung city transport system , then analysis the influence of motor vehicle exhaust emissions , especially gas CO , SO2 and NO2 air quality in urban and sub-urban aras.The results of this study will show how much influence the motor vehicle exhaust emissions on ambient air quality in urban and sub-urban areas . It is expected Bandar Lampung city government can adopt policies to reduce air pollution from transportation Activities.